Development and validation of HPLC method for analysis of indolocarbazole derivative LCS-1269 - Zoya Shprakh; Andrei Budko; Dmitry Kozin; Lydia Ektova; Dmitry Gusev; Vladimir Reshetnyak; Olga Nesterova (Pensoft Publishers, 2021)
Indolocarbazole glycosidic derivative LCS-1269 with significant antiproliferative activity has been synthesized in N.N. Blokhin National Medical Research Center of Oncology. To control the quality of the substance, the chromatographic method of the assay was created and validated. The technique was carried out in a gradient mode using mobile phases consist of acetonitrile, trifluoroacetic acid and purified water. The specificity of the method was shown by checking of test solutions and the special solvent chromatograms. The method linearity was confirmed, and the parameters of linear dependence have been estimated, and the relationship was described by the equation: y = 49.23× - 35.51 with correlation coefficient 0.9998. The method's precision was determined as the repeatability with a relative error of the mean 1.49% and was 2.433 ± 0.036. Was shown, that the results obtained in the intermediate precision estimation were not burdened with a systematic error. The detection limit and quantitation limit were calculated based on the linear relationship data as 3.15 μg/mL and 9.57 μg/mL, respectively. Sensitive HPLC method for LCS-1269 assay in substance has been developed and validated.